Patient self-assessment of hospital pain, mood and health-related quality of life in adults with sickle cell disease. Issue 4 (2nd July 2012) - Anie, Kofi A; Grocott, Hannah; White, Lauren; Dzingina, Mendwas; Rogers, Gabriel; Cho, Gavin
Abstract : Introduction: Acute pain is a hallmark of sickle cell disease (SCD) for which frequent hospital admissions may be required, affecting the quality of life of patients. Objectives: To characterise the relationship between adult patient self-reported sickle cell pain, mood and quality of life during and after hospital admissions. Design: Longitudinal study across three time-points. Setting: Secondary care, single specialist sickle cell centre. Participants: 510 adult patients with SCD admitted to hospital daycare or inpatient units. Outcome measures: Self-assessments of pain, mood and health-related quality of life with health utility (measured on the EQ-5D) on admission, before discharge and at 1-week postdischarge. Results: Mood, general health and quality of life showed significant steady improvements with reduction of pain in patients with SCD on admission to hospital, before discharge and at 1-week follow-up (p<0.01). Health utility scores derived from the EQ-5D showed a negative association with pain in regression analysis over the three time-points. Conclusion: Examining health-related quality of life and health utility in relation to pain during hospital admissions is valuable in terms of targeting appropriate psychological interventions within the context of a multidisciplinary approach to managing sickle cell pain. This has implications for healthcare costs.